Insulation Materials in Context of Sustainability - Almusaed, Amjad; Almssad, Asaad (IntechOpen, 2016)
This book gives information and guidance on important subjects. It presents the major and efficient applications for efficient insulation materials. The book is divided into two parts. Part I discusses ecological insulation materials. In this part, the three sub-subjects are drafting, Unconventional insulation materials, Jute-Based Insulation Material, and Possible Applications of Corn Cob as a Raw Insulation Material. Part II: discusses Practical Applying and Performance of Insulation Materials (case studies), where three sub-subjects are drafting seismic aspects of the application of thermal insulation boards beneath the building's foundations, flammability of bio-based rigid polyurethane foam thermal insulation, and the review of some commonly used methods and techniques to measure the thermal conductivity of insulation materials.